RPGR gene therapy presents challenges in cloning the coding sequence - Martinez-Fernandez De La Camara, C; Cehajic-Kapetanovic, J; MacLaren, RE (Taylor and Francis, 2019)
Introduction: Currently, there are three Phase I/II clinical trials based on gene therapy ongoing to test different AAV.RPGR or deleted RPGR vectors on patients affected by X-linked retinitis pigmentosa. These three vectors differ in the adeno-associated viral (AAV) vector capsid used, and the coding sequences: two contain codon optimized versions of RPGR which give the full-length protein, whilst the third uses a wild-type sequence that contains a large deletion encoding part of the functional domain of the RPGR protein.